Do Resilience and Social Support Moderate the Association between Race-Related Stress on Black Women’s Reports of Trauma Symptoms? - Williams, Tiffany R. (Race and social problems, 2024)
Black women uniquely experience a myriad of intersecting oppressions along with racial discrimination that increases their vulnerability to trauma. Experiences of racial discrimination manifest as race-related stress, or worse an emotional wound, race-related trauma. Protective factors that facilitate coping for black women are resilience and social support. Under investigation were black women’s experiences of racial stress, specifically, perseverative cognition (PC) and anticipatory race-related stress (ARRS), and trauma symptoms. PC and ARRS derive from the Prolonged Activation and Anticipatory Race-Related Stress Scale. The moderating effects of resilience and social support were also examined. Data were collected from 216 black female students at a Historically Black College or University. The findings indicate (1) PC was associated with higher trauma symptoms (ß = 4.46; p < .001); (2) ARSS was positively associated with trauma symptoms (ß = 4.82; p < .001); (3) Social support (ß = − 2.04; p < .001) and resilience (ß = − 2.80; p < .05) moderated the association between ARRS and trauma symptoms such that the association between racial stress and trauma symptoms was stronger under the condition of low social support and resilience. Treatment must include culturally relevant interventions and capitalize on protective factors to facilitate healing for black women.